Punishment without trial: the past, present and future of reeducation through labor in China. (2nd January 2016) - Jiang, Su
Abstract : Reeducation through Labor or laojiao was "an institution with Chinese characteristics" that deprived people of liberty for up to four years without trial. Chinese authorities and academics classified laojiao as an "administrative sanction", but in essence it was a criminal punishment. Originating in the political Chaos of the mid-1950s, laojiao was used to crack down on "enemies" in the early years of the PRC. It was reconstructed and revitalized in the early 1980s. Since then, laojiao was expanded and abused to target various forms of conduct that was seen to disrupt social stability. However, critics charged liaojiao violated international human rights conventions and domestic substantive law and procedural law in China and lacked legitimacy. For these reasons, several reform proposals were put forward. Chinese authorities formally abolished laojiao in 2013. However, many features of laojiao were channeled to new forms of punishment, rather than eliminated. To some extent, the abolition of laojiao changes merely the form but not the substance.